BET inhibition revealed varying MYC dependency mechanisms independent of gene alterations in aggressive B-cell lymphomas - Loris Delrieu; Sieme Hamaidia; Emilie Montaut; Andrea Cecilia Garcia-Sandoval; Camille Teste; Patricia Betton-Fraisse; Thierry Bonnefoix; Sylvain Carras; Rémy Gressin; Christine Lefebvre; Jérôme Govin; Anouk Emadali (Clinical Epigenetics)
Abstract Background MYC-driven lymphomas are a subset of B-cell lymphomas characterized by genetic alterations that dysregulate the expression of the MYC oncogene. When overexpressed, typically through chromosomal translocations, amplifications, or other mechanisms, MYC can drive uncontrolled cell growth and contribute to cancer development. MYC-driven lymphomas are described as aggressive entities which require intensive treatment approaches and can be associated with poor prognosis. In the absence of direct MYC-targeting therapy, epigenetic drugs called BET inhibitors (BETi) were shown to reduce MYC levels by disrupting BRD4-dependent transcription associated with the expression of MYC, as well as other oncogenes. Here, we used BETi as molecular tools to better understand oncogenic dependencies in a panel of cell line models of MYC-driven B-cell lymphoma selected to represent their genetic heterogeneity. Results We first showed that, in these models, MYC expression level does not strictly correlate to the presence of gene alterations. Our data also demonstrated that BETi induces similar growth arrest in all lymphoma cell lines independently of MYC mutational status or expression level. In contrast, BETi-induced cell death was only observed in two cell lines presenting the highest level of MYC protein. This suggests that some MYC-driven lymphoma could present a stronger dependency on MYC for their survival which cannot be predicted on the sole basis on their genetics. This hypothesis was confirmed by gene invalidation experiments, which showed that MYC loss recapitulates the effect of BETi treatment on both cell proliferation and survival, confirming MYC oncogene dependency in models sensitive to BETi cytotoxicity. In contrast, the growth arrest observed in cell lines resistant to BETi-induced apoptosis is not mediated through MYC, but rather through alternative pro-proliferative or oncogenic pathways. Gene expression profiling revealed the basal activation of a specific non-canonical WNT/Hippo pathway in cell death-resistant cell lines that could be targeted in combination therapy to restore BETi cytotoxicity. Conclusion This work brings new insights into the complexity of MYC-dependencies and unravels a novel targetable oncogenic pathway in aggressive B-cell lymphomas.